Importance of hedgehog interacting protein and other lung function genes in asthma - Li, Xingnan (2011)
BACKGROUND: Two recent large meta-analyses of genome-wide association studies of lung function in general populations of European descent identified 11 candidate genes/regions. The importance of these genes in lung function in whites and African Americans with asthma is unknown. OBJECTIVES: To determine if genes that regulate lung function in general populations are associated with lung function abnormalities in subjects with asthma from different racial groups. METHODS: SNPs were tested in five asthma populations (n = 1,441) for association with pulmonary function and meta-analysis was performed across populations. The SNPs with the highest significance were then tested for association with bronchodilator reversibility and bronchial hyperresponsiveness to methacholine (BHR). A joint analysis of consistently replicated SNPs was performed to predict lung function in asthma. RESULTS: Hedgehog interacting protein (HHIP) on chromosome 4q31 was associated with lung function in all five populations, rs1512288: P(meta) = 9.62E-05 and 3.23E-05 for ppFEV(1) and ppFVC, respectively. The SNPs in HHIP were also associated with reversibility (P < 0.05) but not BHR. Because of differences in linkage disequilibrium in the African-American subjects, the most relevant SNPs in HHIP were identified. A subset of normal lung function genes, including HHIP, family with sequence similarity 13, member A (FAM13A), and patched homolog 1 (PTCH1), together predict lung function abnormalities, a measure of severity in whites and African Americans with asthma. CONCLUSION: A subset of the genes, including HHIP, which regulate lung function in general populations are associated with abnormal lung function in asthma in non-Hispanic whites and African Americans.